An integrated device for rapid analysis of indoor air quality in farms: The cases of milking parlors and greenhouses for baby leaf cultivation. (1st October 2022) - Tugnolo, Alessio; Beghi, Roberto; Cocetta, Giacomo; Finzi, Alberto
Abstract: The agricultural sector is responsible for polluting emissions originating from various sources, that impact on the environment and on human health. The negative effect of the emissions can have a greater effect if they originate in confined areas which can therefore bring gas concentrations to critical levels of tolerability for hosts (both workers and animals). In this regard, the contexts that can present major problems are attributable to the livestock activities and protected crop cultivations, in which agricultural machinery is used. To mitigate the emissions of polluting gases and improve indoor air quality, it is important to carry out effective monitoring procedures that can lead to the implementation of targeted corrective measures. For this purpose, it is necessary to use devices able to continuously detect the air gases concentrations in real-time. At the same time, the devices should be cheap, user-friendly and reliable. The novelty lies in the application of this technology in a context where currently no systems for monitoring and active control of air quality are used. This study reports the application of a prototype device (integrated device for air quality measure – Indaqum) based on low-cost sensors to evaluate the performance of two different agricultural contexts and for which more insights are needed, the milking parlors and greenhouses for baby leaf cultivation. The statistical analysis shows the reliability of measures performed with Indaqum, compared to the reference measuring systems adopted (Drager tubes) resulting to properly measure NH3, CO2 and NO2 air concentrations. In both the case studies examined, a good ventilation proved essential to keep low gas concentrations in the air. Highlights: Gas emissions in confined areas can reach critical levels of concentrations. More insights are needed for milking parlors and greenhouses for baby leaves. A prototype device with cheap sensors to monitor continuously air quality was used. It achieved high performance for NH3, CO2 and NO2 detecting small variations in gases. Good ventilation is essential to maintain low gas concentrations even in cold periods.